Significance of pollinators for sustainable agriculture and biodiversity conservation - Rai, Vijay Laxmi; Singh, Rudra Pratap; Singh, Sameer Kumar (Indian Horticulture, 2020)
From the familiar potted plant to growing a wide range of seed producing botanical species relies primarily on pollination to sustain their existence. Pollinators are essential for orchard, horticultural and forage production, as well as the production of seed for many root and fiber crops which reciprocate by offering food and shelter. Crop pollination is the key to food production and security which has been little understood, however it has a great significance for biodiversity conservation at essentially no cost. As farm fields have become larger, production systems have intensified, and the use of agricultural chemicals that impact beneficial insects such as pollinators has increased. As a result pollination services are showing declining trends in a number of instances. A major barrier to enhance pollinator conservation and management is the existing knowledge base which is scattered and often inaccessible to people who need it for introducing appropriate pollinatorfriendly practices into agricultural management.